Experimental Study on the Factors of the Oil Shale Thermal Breakdown in High-Voltage Power Frequency Electric Heating Technology - Sun, Youhong; Liu, Shichang; Li, Qiang; Lü, Xiaoshu (MDPI, 2022)
We conducted an experimental study on the breakdown process of oil shale by high-voltage power frequency electric heating in-situ pyrolyzing (HVF) technology to examine the impact mechanisms of the electric field intensity, initial temperature, and moisture content on a breakdown, using Huadian oil shale samples. A thermal breakdown occurred when the electric field intensity was between 100 and 180 V/cm. The greater the electric field intensity, the easier the thermal breakdown and the lower the energy consumption. The critical temperature of the oil shale thermal breakdown ranged from 93 to 102 °C. A higher initial temperature increases the difficulty of breakdown, which is inconsistent with the classical theory of a solid thermal breakdown. The main factor that affects the electrical conductivity of oil shale is the presence of water, which is also a necessary condition for the thermal breakdown of oil shale. There should be an optimal moisture content that minimizes both the breakdown time and energy consumption for oil shale’s thermal breakdown. The thermal breakdown of oil shale results from heat generation and dissipation. The electric field intensity only affects the heat generation process, whereas the initial temperature and moisture content impact both the heat generation and dissipation processes, and the impacts of moisture content are greater than those of the initial temperature.
Keywords: oil shale; in-situ pyrolysis; high-voltage power frequency electric heating technology; thermal breakdown; electric field intensity; initial temperature; moisture content; fi=Energiatekniikka|en=Energy Technology|